Cut off Value of Red Cell Distribution Width (RDW) in Screening and Diagnosis of Iron Deficiency Anemia and b Thalassemia Trait - Tayab, Md Abu; Hoq, Md Ariful; Begum, Masuma (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: The most concerning consequences of iron deficiency in children are the alterations of cognitive, motor, and behavioral performance. Persistent neurocognitive changes despite iron repletion have increased the importance of prevention and early detection of iron deficiency. Objectives: To evaluate the cut off value of red cell distribution width (RWD) in the screening and diagnosis of iron deficiency anemia (IDA) and â thalassemia trait (BTT). Methods: It is a cross sectional study performed at Dhaka Shishu (Children) Hospital from July 2006 to July 2008. Total 52 patients, age ranged from 1-12 years were included in the study. Among them 27 cases were IDA and 25 cases were BTT. Complete blood count (CBC), serum ferritin and hemoglobin (HB) electrophoresis were measured. The sensitivity, specificity, positive and negative predictive value of differential and cutoff value for RDW discrimination index in differentiation between IDA and BTT were performed. Results: Age ranged from 1-12 years. In IDA group male were found 16(59%), female were 11(41%) and in BTT group male were 15(60%), female were 10(40%). The Hb% value in IDA group was significantly (p<0.0001) lower than value for BTT. An elevation of RBC distribution width (>14.6) in IDA had a sensitivity of 81%, specificity of 84%, positive predictive value (PPV) of 85% and negative predictive value (NPV) of 81%; value of RBC distribution width (<14.6) in BTT had a sensitivity of 84%, specificity of 81%, positive predictive value (PPV) of 81% and negative predictive value (NPV) of 85%. An elevation of RBC distribution width (>16) had a sensitivity of 67%, specificity of 92%, and positive predictive value (PPV) of 90% in distinguishing iron deficiency anemia from thalassemia trait. Moreover, eleven (11) of 27 patients with iron deficiency had RBC distribution width values greater than 18 compared to one (1) of the patients with thalassemia trait. An elevation of RBC distribution width ³18 specificity of 96% and positive predictive value (PPV) of 92%. Conclusion: The rersult of the study, in patients with microcytic hypochromic anemia, RDW value e³14.6% and Hb level< 10gm/dl, iron deficiency is the most likely diagnosis. RDW value (>16) is a reliable diagnostic tool in differentiation between IDA and BTT. Red cell distribution width (RDW) above 16% is the best index of IDA. DS (Child) H J 2021; 37(1): 51-58